2019
DOI: 10.1080/21691401.2019.1640716
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized selenium nanoparticles enhance the anti-EV71 activity of oseltamivir in human astrocytoma cell model

Abstract: Enterovirus 71 (EV71) which commonly caused the hand-foot-mouth disease (HFMD) has become one of public health challenges worldwide. However, no effective vaccines or drugs for this disease has been developed. Thus, there is an urgent need to find a new strategy for treating the EV71 infection. Oseltamivir (OT) is an effective antiviral agent, but continuous use of oseltamivir leads to a diminished therapeutic effect in the clinic. In order to improve the antiviral activity of oseltamivir, oseltamivir was load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Apart from its low toxicity, affordability and high bioavailability, selenium also has protective, antioxidative, anticancer, antibacterial and antiviral effects (Pietka‐Ottlik et al ., 2010). At present, the antiviral activity of selenium has been tested only in a few viruses relevant to human diseases (Li et al ., 2017; Li et al ., 2018; Lin et al ., 2018; Liu et al ., 2020; Ramya et al ., 2015; Zhong et al ., 2019), and most studies were performed at the cell level. In this study, the red elemental selenium (Se 0 ) purified from fermentation products of H. camelliae WT00C was used to culture EPC cells or feed crucian carp and zebrafish, and then its antiviral effects were tested after SVCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its low toxicity, affordability and high bioavailability, selenium also has protective, antioxidative, anticancer, antibacterial and antiviral effects (Pietka‐Ottlik et al ., 2010). At present, the antiviral activity of selenium has been tested only in a few viruses relevant to human diseases (Li et al ., 2017; Li et al ., 2018; Lin et al ., 2018; Liu et al ., 2020; Ramya et al ., 2015; Zhong et al ., 2019), and most studies were performed at the cell level. In this study, the red elemental selenium (Se 0 ) purified from fermentation products of H. camelliae WT00C was used to culture EPC cells or feed crucian carp and zebrafish, and then its antiviral effects were tested after SVCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Zhong et al . (2019) used OTV to decorate SeNPs and found that the functionalized SeNPs enhanced the anti‐EV71 (human enterovirus 71) activity of OTV in human astrocytoma cell model. Ramya et al .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the antiviral effect of metallic nanoparticles is due to a synergistic effect with other chemical compounds. Selenium nanoparticles (SeNPs) enhance the anti-EV71 activity of oseltamivir in the human astrocytoma cell model [54].…”
Section: Antiviral Activity Of Metallic Nanoparticlesmentioning
confidence: 99%
“…20 nM oseltamivir); 24–48 h 9.8 μM (incl. 20 nM oseltamivir) - [ 64 ] Selenium 100 Chemical Vero cells 15.625 μM; 48 h 15.625 μM - [ 65 ] Chikungunya Silver 64–151 Biological (plant extract) Vero cells 1000–31.25 μg/mL; 5 days 62.5 μg/mL - [ 75 ] Silver 50–120 Biological (plant extracts) Vero cells 7.81–1000 μg/mL; 5 days 31.25, 125, and 250 μg/mL - [ 76 ] Zinc oxide - Precipitation method MA104 cells (African green monkey fetal kidney) 0.5–6.5 pg/mL; 4 days 10-fold decrease in viral load: 2.5 pg/mL - [ 77 ] Dengue Gold-small interfering RNA 12.92–43.25 nm Chemical Vero cells 20–80 nM; 48–72 h 80 nM - [ 105 ] Silver 30–70 nm Biological (plant extract) Vero cells 10–100 μg/mL; 48 h 30 μg/mL - [ 108 ] Silver 35–65 nm Biological (alga) Vero cells 6.25–50 μg/mL; 48 h IC 80 : 50 μg/mL IC 50 : 12.5 μg/mL - [ 107 ] Silver 100 nm Biological (seed extract) Vero cells 10–40 μg/mL; 6, 24, 24 h 20 μg/mL - [ 109 ] Herpes simplex Gold …”
Section: Antiviral Potential Of Metal Nanoparticles Against Differentmentioning
confidence: 99%
“…Selenium NPs were found to be active against enterovirus. Also, selenium NPs conjugated with oseltamivir inhibited enterovirus activity by reducing the production of ROS in human astrocytoma cells [ 64 ]. Li et al [ 65 ] reported that selenium NPs inhibited the Jun amino-terminal kinase (JNK) signaling pathway, p38 kinase, and ROS production, resulting in reducing the viral protein synthesis and viral yield [ 66 ] and controlling ROS [ 67 ], which promoted antiviral activity against enterovirus.…”
Section: Antiviral Potential Of Metal Nanoparticles Against Differentmentioning
confidence: 99%